Analisis Pengaruh Keberadaan Jalan Hertasning Baru Terhadap Perubahan Pemanfaatan Lahan di Kecamatan Somba Opu Kabupaten GowaKota Sungguminasa sebagai Ibukota Kabupaten Gowa telah ditetapkan sebagai salah satu pusat dalam sistem pengembangan kota terpad - Risnawati K (LOSARI : Jurnal Arsitektur Kota dan Pemukiman, 2016)
Sungguminasa City as the Capital of Gowa Regency has been designated as one of the centers in the MAMMINASATA integrated city development system, so that Sungguminasa City has a dual function and role where the primary function is the center of administrative activities of the Gowa Regency government, as the center of the development of Gowa Regency, as a sub-center of the development of Makassar City for the development of residential areas and as a center for agricultural research activities in the Gowa Regency area. The existing condition of Jalan Hertasning Baru, Somba Opu District is currently experiencing the dynamics of the development of activities, especially economic activities that are increasing. However, the availability of land is limited, so land is a very important need. The intensity of land use that leads to changes in land use is getting higher. If it is not regulated and directed, land use that has an impact on changing land functions will cause various problems. This study aims to; (1) To identify how the change in land function in Somba Opu District after the existence of Jalan Hertasning Baru, (2) To identify what changes in land function occurred as a result of the existence of Jalan Hertasning Baru, (3) To identify how the existence of Jalan Hertasning Baru terminated the change in land function in Somba Opu District. This research is descriptive. Data collection is carried out through observation, interviews, and documentation. The data was analyzed through quantitative analysis. The results of the study show that the change in land function that occurred in Somba Opu District after the existence of Jalan Hertasning Baru is the rapid development which causes an increase in living needs, including the need for land resources. The need for land in Somba Opu District is increasing in line with population growth and accompanying socio-economic activities, Changes in land function that occur as a result of the existence of Jalan Hertasning Baru, namely the change in the function of plantation land into developed land, namely residential and commercial land, where if this change in land use is not immediately addressed, it will result in urban chaos that can have an impact negatives such as increasing air pollution and decreasing catchment areas that can trigger flooding.